Upaya Meningkatkan Kreativitas Dan Hasil Belajar Matematika Dengan Model Pembelajaran Flipped Classroom Di Kelas XII SMK N 1 Gedangsari - Anita Dwi Lestari; Istiqomah Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2018)
This classroom action research aims to improve the creativity and learning outcomes of mathematics class XII SMK N 1 Gedangsari academic year 2017/2018 using Flipped Classroom learning model. From the research result, the average creativity of the students before the action is 61.45% and then in the first cycle increased to 63.39% and in the second cycle increased to 72.42%. In the achievement of KKM value in pre cycle to cycle 1 increased by 12.90% from 48.39 % to 61.29% and in cycle 1 to cycle 2 increased by 19.35% from 61.29% to 80.65%.